Synthesis, characterization and optical studies of conjugated Schiff base polymer containing thieno[3,2-b]thiophene and 1,2,4-triazole groups - Çetin, A.; Korkmaz A.; Kaya E. (Elsevier B.V., 2018)
A conjugated polyschiff base (poly(N-thieno[3,2-b]thiophen-2-yl)methylene)-1H-1,2,4-triazol-5-amine) poly(TTMA)) was synthesized by condensation polymerization between thieno[3,2-b]thiophene-2,5-dicarboxaldehyde and 3,5-diamino-1,2,4-triazole. The poly(TTMA) was characterized by FT-IR, 1H NMR, 13C NMR spectra and thermal analysis. The number average molecular weight (Mn) and polydispersity index of the poly(TTMA) were determined by gel permeation chromatography (GPC). In addition, the optical properties of the poly(TTMA) solutions were investigated at different molarities. The band gap Eg value of the poly(TTMA) decreased with the increasing molarity. The absorption band edge values of the poly(TTMA) decreased as the molarity increased. The average transmittance values of the poly(TTMA) increased with the increasing molarity and the highest values of molar extinction coefficient also were found in the near ultraviolet region. Its values decreased with the increasing molarity. These results showed that the poly(TTMA) can be used for the fabrication of many optoelectronic devices due to its suitable optical properties and low optical band gap. © 2017 Elsevier B.V.
Keywords: Absorption average transmittance; Absorption band edge; Conjugated polyschiff base; Optical band gap